Performance Analysis of Diesel Engine Simulation Into CNG Engine - Permana, ade Indra (Universitas Ibn Khaldun Bogor, 2022)
The fundamental problem in meeting fuel consumption for the operation of diesel engines is in terms of costs and ensuring the availability of the fuel. So that the idea of using alternative fuels other than diesel fuel arises. And the recommendation is gas fuel (compressed natural gas) for several reasons including cheaper prices and Indonesia has abundant natural gas reserves. Because the properties of CNG and diesel oil are different, it is necessary to modify the diesel engine before being able to use alternative gas fuels. And in this journal, what is analyzed is the performance of diesel engines and diesel engines that have been modified into CNG engines connected to RPM. The analyzed performance includes brake power, brake torque, fuel consumption, and volumetric efficiency. The analysis process is carried out through a simulation using the GT-Power software. From the simulation, it is known that the use of CNG as a fuel reduces exhaust emissions even though it reduces engine performance in terms of power, torque, BMEP. And tends to increase fuel consumption.